A Study Of Flow Characteristics Along Atawau Spillway Model - Keesan, Farhain Afiqah Mohd (Universiti Sains Malaysia, 2022)
Spillway is a structure that is included in most dams which helps to control the water flow, by allowing water to discharge via the spillway channel and prevent the dam from overflowing. Spillway is designed with the aid of penstock and pumps. The outlet of the spillway downstream from the dam is connected to the intake of the spillway upstream. This study reported the changes in flow pattern with the application of penstocks and the velocity of flow at the spillway model structure with scale 1: 30. Several cases will be conduct by differing the penstock opening depth while allowing water to flow where the velocity readings of water will be recorded using Nixon Streamflo Velocity Meter. Water flow from upstream to downstream will create high kinetic energy. Hence, high velocity of water flow will occur which may lead to several problems such as sedimentation, cavitation damage, and formation of vortices. These problems can cause the structure to meet failure. Therefore, the velocity flow profile is identified by using Surfer 3D software to obtain the velocity contour mapping as the output from the data collection. The increase in the velocity depends on the spillway width and depth of penstock. The purpose of achieving the velocity contour on the water flow at the spillway is to make some modifications in the future on that model so that the model can be used effectively as guidance to construct a real spillway dam in a real environment.